Alternatif Kebijakan Pengelolaan Guru Pendidikan Agama pada Sekolah - Suprapto Suprapto (Badan Litbang dan Diklat Kementerian Agama RI, 2011)
AbstractThis research provides several alternatives regarding policy on Islamic education teacher management at school; firstly, appoinment authority and GPAI development at school becomes collective responsibility between the Ministry of Relogious Affairs and Local Government, ehereas substance development constitutes the authority of the Ministry of Religious Affairs, whilst administration development, career development, prosperity allowance and DP3 assesment still become responsibillity of the Local Government. Secondly, the appointment authority and development on GPAI at school become a full responsibility of the Local Government whereas the substance development still becomes responsibility of the Ministry of Religious Affairs and the administration developmnet, career development, prosperity allowance and DP3 assessment still become responsibility of the Local Government. The policy requires legal foundation and clear work management either its appointment or development.Â AbstrakPenelitian ini memberikan beberapa alternatif tentang kebijakan pengelolaan guru pendidikan agama Islam pada sekolah; pertama, kewenangan pengangkatan dan pembinaan GPAI pada sekolah menjadi tanggungjawab bersama antara Kementerian Agama dan Pemerintah Daerah, sedangkan pembinaan substansi merupakan kewenangan Kementerian Agama, sementara pembinaan administrasi, pengembangan karier, tunjangan kesejahteraan dan penilaian DP3 tetap menjadi tanggungjawab Pemerintah Daerah. Kedua, kewenangan pengangkatan dan pembinaan GPAI pada sekolah sepenuhnya menjadi tanggung jawab Kementerian Agama. Ketiga, kewenangan pengangkatan GPAI pada sekolah menjadi tanggungjawab penuh Pemerintah Daerah sedangkan pembinaan substansi tetap menjadi tanggungjawab Kementerian Agama dan pembinaan administrasi, pengembangan karier, tunjangan kesejahteraan dan penilaian DP3 tetap menjadi tanggungjawab Pemerintah Daerah. Kebijakan tersebut membutuhkan landasan hukum dan tata kerja yang jelas, baik dalam pengangkatan maupun pembinaannya.